Identification of Health and Safety Performance Improvement Indicators for Small and Medium Construction Enterprises: A Delphi Consensus Study - Agumba, Justus N.; Haupt, Theo C. (Richtmann Publishing, 2012)
This study sought to identify and validate a comprehensive set of health and safety (H&S) leading indicator metrics that willenable small and medium construction enterprises (SMEs) personnel to monitor the level of H&S performance in their projects. TheDelphi approach was used where the opinion of H&S experts, academics and industry practitioners were canvassed on 64 potentialindicator metrics, categorized in 10 elements or leading indicators that will enable H&S performance improvement e.g. reduction inaccidents, injuries, diseases but to name a few. The experts rated each indicator metric on a 10-point Likert scale of impact, where 1= nomajor impact or 10% impact and 10 = major impact or 100% impact. Consensus was reached on 32 indicator metrics after foursuccessive rounds of Delphi if the indicators attracted final scores of, percentage median impact of 90% to 100% which is 9.00 to 10.00median rating and over 50% of respondents rating the indicator metrics in the band of 9.00 to 10.00 or 90% to 100% impact to improveH&S performance. The experts had the opportunity to reconsider their scores informed by the group median score in rounds 2, 3 and 4.The limitation of the study was the reliance of a structured questionnaire in the first round as experts were not allowed to add any newindicators, until the fourth round. This study contributes to the H&S body of knowledge where no consensus has been reached pertainingto the indicator metrics that have major impact to improve H&S performance at project level of construction SMEs in South Africa.